Observation of Wear Characteristic on Razor Blades with Different Materials and Lubricants - Dedison Gasni; Haznam Putra; Muhammad Azam (Department of Mechanical Engineering, Universitas Andalas, 2023)
Wear of razor blades often occurs when a man shaves his facial. In this paper, the observation of wear characteristic with different types of material and lubricant is investigated. The experiment was conducted on 6 students of the Mechanical Engineering study program with uniform beards and mustaches for 6 weeks. Each week, the wear from the surface of each blade was observed using an optical microscope. Two types of razors were investigared with different materials based on the price, which are consisted of cheap razor (type-A) and expensive razor (type-B), each of which has 3 blades. There were three types of lubricants used, namely: water, liquid soap, and foam. The result shows that type-B razor is better than type-B razor because the material has a high carbon content based on chemical content from testing with Energy Dispersive X-Ray (EDX). Foam lubricant can slow down the wear on razor blades. The 1st blade razor wears out faster than the 2nd and 3rd bladem, respectively.